Methylmercury Accumulation in Rice Grain (Oryza sativa L.): Environment and Genotype Controls - Rothenberg S. E. (E3S Web of Conferences, 2013)
In 2010, 50 indica rice varieties were cultivated in three sites in southwestern China along a contamination gradient (background, moderately-contaminated and highly-contaminated sites) to determine environment and genotype controls on MeHg accumulation in polished white rice and bran. Rice grain MeHg concentrations were significantly higher in the moderately-contaminated site compared to the other two sites (ANOVA, p<0.0001). Lower rice grain MeHg concentrations in the highly-contaminated site possibly reflected differences in surface water pH (highly-contaminated site: pH 11, other two sites: pH 7.6-8.0). More alkaline conditions at the highly-contaminated site possibly decreased the bioavailability of MeHg and/or other trace elements, thus lowering the uptake of MeHg from paddy soil to rice grain. Polished white rice MeHg concentrations were significantly associated with rice genotype (p<0001), indicating there may be genetic markers associated with the translocation of MeHg from the maternal tissue to the filial tissue (i.e., from the bran to the polished grain). Additionally, low MeHg-accumulating rice varieties were identified, which decreased MeHg exposure up to 69%, and may be recommended to farmers to mitigate MeHg accumulation in rice grain.